(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This study investigates the synthesis and application of modified polyvinyl chloride (PVC)-based sorbents for the removal of heavy metal ions from industrial wastewater. PVC was chemically modified with various amines, such as diethylamine, monoethanolamine, and diphenylamine, to enhance its sorption capacity. The modified sorbents were tested for their ability to adsorb metal ions, including copper (Cu²⁺), cadmium (Cd²⁺), and zinc (Zn²⁺), under both static and dynamic conditions. The results indicate significant improvements in the adsorption efficiency and thermal stability of the sorbents, demonstrating their potential for industrial applications.